2014
DOI: 10.1007/s10393-014-0992-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-Run Relative Importance of Temperature as the Main Driver to Malaria Transmission in Limpopo Province, South Africa: A Simple Econometric Approach

Abstract: Malaria in Limpopo Province of South Africa is shifting and now observed in originally non-malaria districts and it is unclear whether climate change drives this shift. This study examines the distribution of malaria at district level in the province; determines direction and strength of the linear relationship and causality between malaria with the meteorological variables (rainfall and temperature) and ascertains their short and long run variations. Spatio-temporal method, Correlation analysis and econometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 50 publications
0
23
1
Order By: Relevance
“…28 showed that incidence rates in Limpopo were related to both temperature and rainfall. However, they also showed that temperature plays a more important role in influencing malaria transmission compared to rainfall 28 . Precipitation and temperature are the most commonly tested climate variables.…”
Section: Introductionmentioning
confidence: 99%
“…28 showed that incidence rates in Limpopo were related to both temperature and rainfall. However, they also showed that temperature plays a more important role in influencing malaria transmission compared to rainfall 28 . Precipitation and temperature are the most commonly tested climate variables.…”
Section: Introductionmentioning
confidence: 99%
“…Diarrhoeal infections were linked in one study to anomalously dry seasons and increases in monthly average maximum temperatures in sub-Saharan Africa. [6] Malaria in Limpopo is more significantly associated with temperature than rainfall, [7] and models suggest a possible expansion in malaria zones in Africa, including SA in the future. [8] Schistosoma worms, the cause of schistosomiasis (including bilharzia), may thrive in warmer water and emergent transmission in previously unaffected areas may occur.…”
Section: Climate Change and Health In South Africamentioning
confidence: 99%
“…Lazenby et al [13] have considered the prediction skill of temperature variability at the seasonal time scale for various time frames (in months) and various lead times and show the utility (and current limitations) of these predictabilities in respect of health applications. This is the approach adopted in a study currently underway in the Mopani district of Limpopo Province which aims to link climate and disease models for malaria, diarrhoea and pneumonia ( Fig.…”
Section: Climate Variability and Change In Southern Africamentioning
confidence: 99%
“…Lazenby et al [13] considered the application of improved seasonal climate forecasting techniques in predicting extreme seasonal temperature in the northern parts of SA, and the direct impact on health. They conclude that the skill of these forecasts is good enough to develop a heat-health warning system for the country.…”
Section: Climate Variability and Change In Southern Africamentioning
confidence: 99%